Tumor characteristics and survival outcomes of women with tamoxifen-related uterine carcinosarcoma - Matsuo, Koji (Gynecol Oncol, 2016)
OBJECTIVE: To examine tumor characteristics and survival outcome of women with uterine carcinosarcoma who had a history of tamoxifen use. METHODS: This is a multicenter retrospective study examining stage I–IV uterine carcinosarcoma cases based on history of tamoxifen use. Patient demographics, tumor characteristics, treatment pattern, and survival outcomes were compared between tamoxifen users and non-users. RESULTS: Sixty-six cases of tamoxifen-related uterine carcinosarcoma were compared to 1009 cases with no history of tamoxifen use. Tamoxifen users were more likely to be older (mean age, 69 versus 64, P < 0.001) and had a past history of malignancy (100% versus 12.7%, P < 0.001). Tamoxifen-related uterine carcinosarcoma was significantly associated with a higher proportion of stage IA disease (48.4% versus 29.9%) and a lower risk of stage IVB disease (7.8% versus 16.0%) compared to tamoxifen-unrelated carcinosarcoma (P = 0.034). Deep myometrial tumor invasion was less common in uterine carcinosarcoma related to tamoxifen use (28.3% versus 48.8%, P = 0.002). On univariate analysis, tamoxifen use was not associated with progression-free survival (5-year rates 44.5% versus 46.8%, P = 0.48) and disease-specific survival (64.0% versus 59.1%, P =0.39).After adjusting for age, past history of malignancy, stage, residual disease status at surgery, and postoperative treatment patterns, tamoxifen use was not associated with progression-free survival (adjusted-hazard ratio 0.86, 95% confidence interval 0.50 to 1.50, P =0.60)anddisease-specific survival(adjusted-hazard ratio0.68,95% confidence interval 0.36 to 1.29, P = 0.24). CONCLUSION: Our study suggests that tamoxifen-related uterine carcinosarcoma may have favorable tumor characteristics but have comparable stage-specific survival outcomes compared to tamoxifen-unrelated uterine carcinosarcoma.